1971
DOI: 10.1002/bjs.1800581025
|View full text |Cite
|
Sign up to set email alerts
|

Surgical treatment of carcinoma of the oesophagus and cardia

Abstract: SUMMARYExperience in the management of a personal series of 837 cases of carcinoma of the oesophagus and cardia is described. It is evident from this that the subject is not a static one. Improvement is occurring and there are good reasons to expect this to continue. The aspects affected by this improvement include morbidity, mortality, the well-being of patients, and the long-term survival. Unfortunately, in the majority of cases, treatment is only palliative, but palliation is good and it relieves the patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
16
0

Year Published

1974
1974
1989
1989

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(18 citation statements)
references
References 17 publications
2
16
0
Order By: Relevance
“…It is the adenocarcinoma which will be considered. Whatever the treatment, this type of carcinoma has a worse prognosis than a squamous cell one in a similar anatomical position (Ellis, 1964;Collis, 1971), and adenocarcinoma of the cardia has a worse prognosis than in other sites in the stomach (Hawley et al, 1970).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It is the adenocarcinoma which will be considered. Whatever the treatment, this type of carcinoma has a worse prognosis than a squamous cell one in a similar anatomical position (Ellis, 1964;Collis, 1971), and adenocarcinoma of the cardia has a worse prognosis than in other sites in the stomach (Hawley et al, 1970).…”
Section: Resultsmentioning
confidence: 99%
“…It is difficult to make a worth-while comparison of personal results of extended total gastrectomy and upper partial gastrectomy because of the inevitable case selection. It is equally difficult to explain the improved results from surgery for carcinoma of the cardia during the past 20 years, even when ample allowance is made for increased experience ; this point has also been discussed by Collis (1971) and McKeown (1972).…”
mentioning
confidence: 99%
“…Of the 185 patients with cancer of the oesophagus who received radiotherapy, four developed radiation myelopathy, a much lower incidence than the operative mortality (Sturdy, 1965;Collis, 1971). More than 30% of patients with cancers other than oesophageal received radiation to the spinal cord while being treated for head and neck tumours, lung cancers, testicular tumours, and lymphomas.…”
Section: Methodsmentioning
confidence: 99%
“…In a patient population with unresectable primary esophageal tu mors, there was a 10% incidence of liver metastases [ 12]. Many authors did not mention the incidence of liver metastases at all and reported only the survival rates in relation to the size and site of the primary tumor [13][14][15][16][17][18], Those who did mention the incidence have generally considered their presence a contra-indication to resect ing the tumor [19][20][21][22], with two exceptions [23,24], The effect of liver metastases on the outcome of these pa tients, however, has not been previously analyzed.…”
Section: Discussionmentioning
confidence: 99%